Uncommon immune-mediated extrahepatic manifestations of HCV infection. (2nd December 2018) - Romano, Ciro; Cuomo, Giovanna; Ferrara, Roberta; Del Mastro, Andrea; Esposito, Sergio; Sellitto, Ausilia; Adinolfi, Luigi Elio
ABSTRACT: Introduction : Chronic hepatitis C virus (HCV) infection has been associated with myriad extrahepatic manifestations, often resulting from aberrant immune responses. Among the most common immune-mediated manifestations of HCV infection, mixed cryoglobulinemia is the best known extra-hepatic complication. Areas covered : Here we review less common extrahepatic manifestations of HCV infection, with ascertained or presumed immune pathogenesis and the role of the new all oral direct-acting antiviral agents. Rheumatologic, dermatologic, ophthalmologic, renal, pulmonary, hematologic, cardiovascular, and neuropsychiatric manifestations of HCV infection have been considered. Expert commentary : Pathogenesis of HCV-induced aberrant immune responses resulting in peculiar clinical manifestations is not restricted to a single mechanism. A sound approach would therefore consider implementation of an etiologic treatment, through use of antiviral medications, to stop upstream in the pathogenic process all the immune mechanisms leading to hepatic and extrahepatic abnormalities. With the recent introduction of interferon-free, direct antiviral agents, capable of warranting cure for nearly all HCV-infected patients subjected to therapy, both common and uncommon extrahepatic manifestations of chronic hepatitis C are expected to no longer constitute a matter of comorbidity in the course of HCV infection.